About how European citizenship is shaping the Nationality Law of the Member States of the Union. Regarding the CJEU of 5 September 2023, Case C-689/21, X - Durán Ayago, Antonia (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
This judgment is the fourth chapter in the relationship between nationality law, which is the exclusive competence of the Member States, and the status of European citizenship. A significant step is taken here, as the principle of proportionality is added to the principle of effectiveness, which implies a progressive shaping of the nationality law of the Member States so as not to infringe European citizenship.
Keywords: Citizenship of the European Union; Nationality Law; principle of proportionality; principle of effectiveness